2016
DOI: 10.1111/obr.12452
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of green tea on risk factors for type 2 diabetes in obese adults – a review

Abstract: Green tea has been associated with positive effects in the treatment of obesity and other associated comorbidities such as type 2 diabetes. These benefits are thought to be related to the anti-inflammatory and antioxidant effects of green tea and to the reduction in body fat percentage exhibited by its bioactive compounds. The predominant active compounds in green tea are flavonoid monomers known as catechins, in particular epigallocatechin-3-gallate, which is the most abundant and most effective catechin in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 85 publications
0
27
0
Order By: Relevance
“…Thus, it is highly likely that the observed thermogenesis is attributable to catechin, rather than caffeine. However, this does not rule out a possible synergistic action between catechins and caffeine (136,137). Collectively, the thermogenic and fat-reducing effects of green tea extract rich in catechins would be attributable to the activation of BAT.…”
Section: Activation and Recruitment Of Bat By Tea Caffeine And Catechinsmentioning
confidence: 99%
“…Thus, it is highly likely that the observed thermogenesis is attributable to catechin, rather than caffeine. However, this does not rule out a possible synergistic action between catechins and caffeine (136,137). Collectively, the thermogenic and fat-reducing effects of green tea extract rich in catechins would be attributable to the activation of BAT.…”
Section: Activation and Recruitment Of Bat By Tea Caffeine And Catechinsmentioning
confidence: 99%
“…An emerging strategy to reduce the prevalence of overweight and obesity is to use natural products such as polyphenols, especially flavan-3-ols which account for up to 80% of total green tea polyphenols and about one-third of its organic fraction. Many studies have indeed shown that flavan-3-ols could be used at nutritional or supra-nutritional concentrations for reducing body weight and risk of type 2 diabetes (Ferreira, Silva, & de Morais, 2016;Hursel, Viechtbauer, & Westerterp-Plantenga, 2009;Jurgens et al, 2012). This could be due in part to the ability of flavanols to inhibit digestive hydrolases, especially salivary and pancreatic alpha-amylases (EC 3.2.1.1) responsible for starch digestion and indirectly for the level of absorbed and metabolized glucose (Hanhineva, Törrönen, Bondia-Pons, & Pekkinen, 2010;Rains, Agarwal, & Maki, 2011;Williamson, 2013;Xiao, Ni, Kai, & Chen, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Tea, derived from the dried tea powder/leaves produced from the fresh buds of the flowering plant Camellia sinensis [15,16], is proposed as one such approach. Literature suggests that tea, especially black, white, and green tea, may positively influence pathology and reduce risk factors associated with AD [17][18][19] and diabetes [20,21] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%